Spermatogenesis and spermatozoal ultrastructure in Metapenaeus monoceros (Fabricius, 1798) - Abraham, Joice; Manissery, Mary K; Sanil, N K (Indian Journal of Fisheries, 2011)
Spermatogenesis in the ‘speckled shrimp’ Metapenaeus monoceros (Fabricius, 1798) was studied employing histological and transmission electron microscopic techniques. Male specimens of the species were classified into three maturity stages based on gross morphology. Spermatozoa of M. monoceros was observed to be unistellate with a spherical main body and a spike. The main body was made up of a central nuclear region, a peripheral cytoplasmic band and an acrosomal cap, which overlaid the nuclear region anteriorly. From the acrosomal cap projected an extended spike towards the anterior of the spermatozoa. The spike and the acrosomal cap together were called the acrosomal vesicle. The average length of the spermatozoa was 6μ m. The main body had a mean diameter of 3.4μ m with the spike measuring 2.6μ m in length.